Clastogenic effects of cigarette smoke and urethane and their modulation by olive oil, curcumin and carotenoids in adult mice and foetuses. (September 2021) - Balansky, Roumen; La Maestra, Sebastiano; Kancheva, Vessela D.; Trofimov, Aleksei V.; Djongov, Lachezar; De Flora, Silvio
Abstract: In spite of the overwhelming epidemiological evidence for cigarette smoke (CS) carcinogenicity, less attention has been paid to the effects of CS as a complex mixture. As assessed in a series of experiments in murine models, the whole-body exposure to mainstream CS induced significant increases of micronucleated cells in the respiratory tract, bone marrow and peripheral blood of adult mice as well as in the liver and peripheral blood of foetuses whose mothers had been exposed throughout pregnancy. Urethane was potently clastogenic in the same cells when injected intraperitoneally. The daily administration of extra-virgin olive oil by gavage produced evident and consistent protective effects in all monitored experimental systems. In contrast, sunflower oil exhibited some adverse effects. Curcumin did not produce any significant effect in the bone marrow of both CS-exposed adults and foetuses but it elicited a dose-dependent protective effect traceable in blood erythrocytes. However, the higher curcumin dose further increased the frequency of micronucleated pulmonary alveolar macrophages. The apparent protective effects produced by lycopene and by a carotenoid mix were overwhelmed by those produced by olive oil, and lycopene even exhibited a worsening effect on the frequency of micronucleated erythroblasts in the bone marrow of urethane-treated adult mice. Graphical abstract: Image 1 Highlights: Cigarette smoke increased micronuclei in mouse respiratory and haematopoietic cells. Urethane was potently clastogenic in the same cells when injected intraperitoneally. Administration of olive oil by gavage consistently produced protective effects. In contrast, sunflower oil exhibited some adverse effects. Curcumin and carotenoids yielded negative or equivocal results.